When an Early Diagnosis of Autism Spectrum Disorder Resolves, What Remains?. (June 2019) - Shulman, Lisa; D'Agostino, Erin; Lee, Samantha; Valicenti-McDermott, Maria; Seijo, Rosa; Tulloch, Elizabeth; Meringolo, Deborah; Tarshis, Nancy
A chart review was performed of 38 children diagnosed with autism spectrum disorder (ASD) by 3 years of age at an inner-city developmental program who subsequently experienced resolution of ASD symptomatology and no longer met diagnostic criteria for ASD at follow-up an average of 4 years later. Demographic, developmental/cognitive data, Childhood Autism Rating Scale, and Autism Diagnostic Observation Schedule data as available were reviewed from the initial diagnostic evaluation and at the time of follow-up. Services received by the children between the time of diagnosis and follow-up, educational setting at the time of follow-up, and emotional/behavioral and learning diagnoses made by the multidisciplinary team at follow-up were reviewed. The findings indicate that residual emotional/behavioral and learning problems were present at follow-up in the vast majority of children in this group and that the majority continued to require educational support.